Inhibition of the Naja naja venom toxicity by polymeric nanoparticles loaded with Leucas aspera methanolic extract - Singh, Priyanka; Jayaraman, Gurunathan (Frontiers in Pharmacology, 2024)
Background: Snakebite is a neglected tropical disease that affects millions of people worldwide. Developing effective treatments can make a significant contribution to global health efforts and public health initiatives. To reduce the mortality due to snakebite, there is an immediate need to explore novel and effective treatment methodologies. In that context, nanoparticle-based drug delivery is getting a lot of attention. Hydrophilic nanoparticles are suitable for the delivery of therapeutic peptides, proteins, and antigens.The present investigation is aimed at evaluating the anti-ophidian potential of the methanolic extract of the ethno-medicinal herb Leucas aspera loaded within chitosan nanoparticles (CNP-LA), against the Indian cobra (Naja naja naja) venom enzymes. For this purpose, nanoparticles were prepared using the ionic gelation method to enhance the efficacy of the extract. The physicochemical and structural features of nanoparticles were investigated using dynamic light scattering (DLS), Fourier Transform Infrared (FTIR), field emission scanning electron microscopy (FE-SEM), and X-ray Diffraction (XRD) techniques.Results: It was found that CNP-LA has an average size of 260 nm with a polydispersity index of 0.132 (PDI) and zeta potential of 34.7 mV, with an encapsulation efficiency of 92.46%. In vitro release study was performed at pH 5.0 and 7.4. Further, in vitro studies indicated that CNP-LA inhibited the phospholipase A2, hemolytic, and caseinolytic activity of Naja naja venom with percentage inhibition of 92.5%, 83.9%, and 94.5%, respectively.This is the first report on the application of herbal methanolic extract loaded within chitosan nanoparticles for neutralizing snake venom enzymes with increased efficiency.